Negotiating from the margins dynamics of women's work in a globalized agricultural economy - Dungo, Nanette Garcia (Diliman, Quezon City University of the Philippines Press, 2007)
"This book examines how the present globalized worksites are opening channels for women to break out from their traditional confinement at home. Through subcontracting, a type of employment that offers flexibility in working hours and workplace, the women are able to contribute to the household income. But with the women prioritizing paid work over domestic chores, the traditional division of labor at home is disrupted, causing conflict between husbands and wives.The book focuses on the women's various response to their husbands' ambivalent attitude toward their rising participating in productive work. As women workers constantly engage in negotiation, compromise, or contestation, they are in the process crafting a new narrative of their own selves, utilizing more empowering initiatives mediating between the demands of tradition and those of globalizing structures."--Back cover.
A discourse on women's work in agriculture -- The rising entrepreneurship and the women subcontractors in the sugar economy : a response to the sugar crisis of the 1980s -- Hacienda women : coping with reproductive and productive work -- The women subcontractors : profiles, work quotas, schedules, compensation, and dynamics of reproductive and productive work -- "Capillarization" of control in women's domestic and productive work -- Women speak : accommodations and resistances as worker-subcontractors and agricultural workers and the emerging dynamics of control -- Negotiating from the margins : women's "space-creating" acts.
UCWS-2014-G-1888 donated by U.P. Press.
Keywords: Women in agriculture -- Philippines -- Negros Island; Subcontracting -- Philippines -- Negros Island; Sex role -- Philippines -- Negros Island